High performance green concrete (HPGC) with improved strength and chloride ion penetration resistance by synergistic action of fly ash, nanoparticles and corrosion inhibitor. (20th February 2019) - Harilal, Manu; Rathish, V.R.; Anandkumar, B.; George, R.P.; Mohammed, M.S. Haji Sheikh; Philip, John; Amarendra, G.
Highlights: A novel HPGC was developed by the partial replacement of cement with FA, nanoparticles and inhibitor in conventional concrete. Evaluation of mechanical and durability properties were carried out on 28 day cured specimens and compared with individual modifications. The synergistic action of fly ash, nanoparticles and inhibitor facilitated the improvement in early age strength and permeability characteristics. The pore size reduction and pore structure refinement resulted in enhanced permeation resistance. Abstract: This work reports a novel high performance green concrete fabricated by incorporating fly ash, nanoparticles and corrosion inhibiting admixture into conventional M45 grade concrete. The optimal composition of the new mix was found to be 40 wt% fly ash, 2 wt% nano-TiO2 and nano-CaCO3 in 1:1 ratio, 2 wt% sodium nitrite based corrosion inhibitor and 56% Ordinary Portland Cement, referred hereafter as CFNI. The properties of CFNI were compared with that of conventional concrete to assess the synergistic role of various additives. Field Emission Scanning Electron Microscope images of CFNI showed a homogeneous distribution of hydration products over the surface. The Confocal Laser Scanning Microscopy images of concrete surfaces and pore size estimation from Mercury Ion Porosimetry confirmed that only gel pores at the nanoscale are present in the CFNI specimens. The compressive strength, flexural strength and split tensile strength of CFNI, measured as per ASTM/Indian standards, showed noticeable enhancement. The chloride ion penetration resistance, carbonation, water permeability and water sorptivity of CFNI was found to be superior as compared to conventional concrete. This study establishes that synergistic action of fly ash, nanoparticles and inhibitor facilitated the improvement in strength and durability of the new green concrete CFNI, which is very promising not only for cost reduction and improved properties of concrete structures, but also reduces energy consumption and green house gas emissions.